Using quality control circle activities to reduce the incidence of the incidence of intraoperative acquired pressure injuries in patients undergoing surgery in the prone position (降低俯卧位手术患者术中获得性压力性损伤发生率的品管圈实践) - WANG Chengwei (王成伟); SU Dan (苏丹); WANG Zhengjian (王政鉴) (中西医结合护理)
Objective To explore the application effect of quality control circle (QCC) activities in reducing the incidence of intraoperative acquired pressure injuries(IAPI)in patients undergoing surgery in the prone position. Methods A QCC team was established, and ten steps of problem-solving QCC activities including determination of theme and activity plan, analysis of facts and data, setting targets, analysis existing conditions and cause, countermeasures and plan improvements, standardization and planning the next steps were conducted, and quality management tools were employed to improve the prevention of pressure injuries in patients undergoing surgery in the prone position. The incidences of IAPI were observed before and after implementation of QCC activities. Results There were 230 patients recruited before implementation of QCC activities and 232 patients recruited after implementation of QCC activities were included as research subjects. The incidence of IAPI in patients undergoing prone position surgery decreased from 6. 52% before the improvement to 1. 72% after the improvement, with a statistically significant difference(P<0. 01). A risk assessment and prevention mechanism for perioperative pressure injuries was constructed and improved. Conclusion The implementation of QCC activities reduced the incidence of IAPI in patients undergoing prone position surgery, enhanced the quality of nursing services, and provided an important reference for constructing a scientific and effective IAPI prevention management system. (目的 探讨品管圈活动在降低俯卧位手术患者术中获得性压力性损伤(IAPI)发生率中的应用效果。方法 成立品管圈小组, 按照问题解决型品管圈活动的步骤, 即主题选定、活动计划拟定、现状把握、目标设定、解析、对策拟定、对策实施与检讨、效果确认、标准化、检讨与改进, 依次推进, 对预防俯卧位手术患者IAPI存在的问题进行改善, 比较品管圈活动实施前和实施后俯卧位手术患者IAPI发生情况。结果 分别选取品管圈活动实施前230例俯卧位手术患者和品管圈活动实施后232例俯卧位手术患者为研究对象, 俯卧位手术患者IAPI发生率由改善前的6. 52%降低至改善后的1. 72%, 差异有统计学意义(P＜0. 01), 构建并完善了围术期患者压力性损伤的风险评估与预防机制。结论 通过开展品管圈活动, 减少俯卧位手术患者IAPI发生率, 提高优质护理服务水平, 为构建科学有效的IAPI预防管理体系提供了重要参考依据。)